The arc of life : evolution and health across the life course - Jasienska, Grazyna; Sherry, Diana S.; Holmes, Donna J. (Springer, 2017)
This book examines ways in which research conducted by biological anthropologists can enrich our understanding of variation in human health outcomes. The book aims not only to showcase the perspective that biological anthropologists bring to the burgeoning field of evolutionary medicine, but to underscore the context of human life history -- especially the concept of evolutionary trade-offs and the ensuing biological processes that can affect health status over the life course. This dual emphasis on life history theory and life cycle biology will make for a valuable and unique, yet complementary, addition to books already available on the subject of evolution and health. The book consolidates diverse lines of research within the field of biological anthropology, stimulates new directions for future research, and facilitates communication between subdisciplines of human biology operating at the forefront of evolutionary medicine.- Resumé vydavatel
Includes index.
Keywords: evoluce (biologie); antropologie; vývojová biologie; evoluční biologie; veřejné zdraví; evolution (biology); anthropology; developmental biology; evolutionary biology; public health; elektronické knihy; sborníky; electronic books; papers of several authors